2017
DOI: 10.1186/s12957-016-1073-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary carcinoma of the cystic duct: a case report and review of classifications

Abstract: BackgroundThe incidence of extrahepatic bile duct malignancies is about 2–3.6% of all gastrointestinal malignancies. Primary carcinoma of cystic duct is a rare condition comprising a fraction of all extrahepatic bile duct malignancies with less than 70 cases reported worldwide. Majority of these cases were reported from East Asia. There is paucity in such case being reported from Indian subcontinent. We present a case of primary carcinoma of the cystic duct encountered during laparoscopic cholecystectomy.Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
1
15
0
5
Order By: Relevance
“…The recommended treatment for BilIN is radical surgery consisting of cholecystectomy with non-anatomical gallbladder fossa resection and excision of the extrahepatic bile duct with regional lymphadenectomy ( 3 , 6 ). The average survival time is 27.2 months, versus just 5.8 months for gallbladder carcinoma and 3.2-11.4 months for other extrahepatic biliary duct cancers ( 6 , 30 ) This is consistent with the finding that symptoms of cystic duct cancer may develop earlier than those of gallbladder cancer ( 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…The recommended treatment for BilIN is radical surgery consisting of cholecystectomy with non-anatomical gallbladder fossa resection and excision of the extrahepatic bile duct with regional lymphadenectomy ( 3 , 6 ). The average survival time is 27.2 months, versus just 5.8 months for gallbladder carcinoma and 3.2-11.4 months for other extrahepatic biliary duct cancers ( 6 , 30 ) This is consistent with the finding that symptoms of cystic duct cancer may develop earlier than those of gallbladder cancer ( 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…Over the last two decades, some researchers have proposed their own classifications of CDC (6). In our clinical work, we found that CDC appears to be commonly associated with hilar involvement, and the extent of tumor invasion in the porta hepatis significantly affects resectability and patient prognosis.…”
Section: Introductionmentioning
confidence: 62%
“…The presence of jaundice, abdominal lump, anorexia, and weight loss are usually indicative of advanced stages. A mucocele of GB in absence of any stone may be early marker for malignancy arising in cystic duct or at neck [ 13 ]. GBC are rarely diagnosed before it has advanced or metastasized [ 14 ].…”
Section: Discussionmentioning
confidence: 99%